2008
DOI: 10.1051/0004-6361:20077921
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon transitions in hydrogen and cosmological recombination

Abstract: We study the two-photon process for the transitions ns → 1s and nd → 1s in hydrogen up to large n. For n ≤ 20 we provide simple analytic fitting formulae to describe the non-resonant part of the two-photon emission profiles. Combining these with the analytic form of the cascade-term yields a simple and accurate description of the full two-photon decay spectrum, which only involves a sum over a few intermediate states. We demonstrate that the cascade term naturally leads to a nearly Lorentzian shape of the two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
154
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(156 citation statements)
references
References 53 publications
2
154
0
Order By: Relevance
“…Dubrovich & Grachev [25] suggested that two-photon transitions from higher levels may have a significant effect on the recombination history. Later computations confirmed this idea [26], and provided an accurate treatement of radiative transfer in the presence of two-photon transitions, as well as a solution for the double-counting problem (which arises for resonant two-photon transitions, already included in the one-photon treatment as "1+1" transitions) [24,27].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Dubrovich & Grachev [25] suggested that two-photon transitions from higher levels may have a significant effect on the recombination history. Later computations confirmed this idea [26], and provided an accurate treatement of radiative transfer in the presence of two-photon transitions, as well as a solution for the double-counting problem (which arises for resonant two-photon transitions, already included in the one-photon treatment as "1+1" transitions) [24,27].…”
Section: Introductionmentioning
confidence: 66%
“…(23)(24)(25)(26)(27)(28), are strictly equivalent to the standard MLA equations presented in the previous section, as was derived in Paper I [Eq. (31) was not derived in that paper and we give a proof in Appendix A 2].…”
Section: General Descriptionmentioning
confidence: 99%
“…Subsequently it was studied by Wong and Scott (2007). This problem was also intensively investigated by Chluba and Sunyaev (2007), who stimulated the appearance of this paper by their numerous questions. The conclusion of the abovementioned works is that the process of two-photon cascade transitions under consideration can lead to corrections of a few tenths of a percent.…”
Section: Introductionmentioning
confidence: 97%
“…The goal of this paper is, in particular, a detailed quantum-mechanical analysis of the problem and an investigation of the line wings, which, as Chluba and Sunyaev (2007) showed, play a significant role in the formation of deviations from the standard picture of recombination.…”
Section: Introductionmentioning
confidence: 99%
“…This regularization is performed by the introduction of the level widths in the energy denominators which otherwise turn to zero for the photon frequencies, corresponding to the cascade resonances. In the QM phenomenological approach only the width of the intermediate state is usually employed for regularization [12], [13], [27]. We call this approach phenomenological since the width is introduced as an phenomenological parameter.…”
Section: Introductionmentioning
confidence: 99%